2015
DOI: 10.1038/ncomms9457
|View full text |Cite
|
Sign up to set email alerts
|

A splicing variant of Merlin promotes metastasis in hepatocellular carcinoma

Abstract: Merlin, which is encoded by the tumour suppressor gene Nf2, plays a crucial role in tumorigenesis and metastasis. However, little is known about the functional importance of Merlin splicing forms. In this study, we show that Merlin is present at low levels in human hepatocellular carcinoma (HCC), particularly in metastatic tumours, where it is associated with a poor prognosis. Surprisingly, a splicing variant of Merlin that lacks exons 2, 3 and 4 (Δ2–4Merlin) is amplified in HCC and portal vein tumour thrombus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…According to our previous RNA-seq analysis, the expression of more than 2000 genes was affected differentially by NBT, and further bioinformatics analysis showed that NBT could affect RNA-binding proteins (RBPs) to regulate alternative splicing (AS) events (data not shown). As one of the post-transcriptional gene regulatory mechanisms, AS enables a single gene to produce multiple messenger RNA variants and distinct protein isoforms, sometimes with different or even opposing roles in the development of tumors, such as proliferation, apoptosis, angiogenesis, drug resistance, and metastasis [23][24][25] . RNA-binding proteins, which are involved in the AS process, have many functions in biologic processes, deregulation of RBP affects every step of cancer development, such as sustained cell proliferation, evasion of apoptosis, avoiding immune surveillance, inducing angiogenesis, and activating metastasis 26,27 ; mounting evidence supports a vital role for RBPs in tumor growth and metastasis [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous RNA-seq analysis, the expression of more than 2000 genes was affected differentially by NBT, and further bioinformatics analysis showed that NBT could affect RNA-binding proteins (RBPs) to regulate alternative splicing (AS) events (data not shown). As one of the post-transcriptional gene regulatory mechanisms, AS enables a single gene to produce multiple messenger RNA variants and distinct protein isoforms, sometimes with different or even opposing roles in the development of tumors, such as proliferation, apoptosis, angiogenesis, drug resistance, and metastasis [23][24][25] . RNA-binding proteins, which are involved in the AS process, have many functions in biologic processes, deregulation of RBP affects every step of cancer development, such as sustained cell proliferation, evasion of apoptosis, avoiding immune surveillance, inducing angiogenesis, and activating metastasis 26,27 ; mounting evidence supports a vital role for RBPs in tumor growth and metastasis [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Although interest in defining cancer‐associated AS continues to increase, the specific biological function harnessed by many of the AS variants in conferring oncogenic advantages remained minimally investigated. To date, there are only a handful of such studies described in HCC . Moreover, although many observational studies have illustrated presence of aberrantly spliced genes in human cancers, the AS landscape of human HCC remains largely unexplored.…”
mentioning
confidence: 99%
“…Moesin-ezrin-radixin-like protein (Merlin) is a tumor suppressor that participates in the regulation of cell proliferation, motility and survival [163]. Merlin is codified by the Nf2 gene, which is heterozygous in mice and is related to the development of highly metastatic malignant tumors [163].…”
Section: Merlinmentioning
confidence: 99%